Utilization of A-carrageenan in the production of dietary fiber-rich sauce for pancit palabok - Suario, Bernadette Abaricia
A formulation for ancit palabok sauce using 4.70% cornstarch was chosen as "control" through sensory evaluation. Simulation of the product profile of the control sauce came out with a formulation using 2.87% λ-carrageenan. Student's t-test showed no significant difference (α = 0.05) between the sensory attributes of the sauces with 4.70% cornstarch and 2.87% λ-carrageenan. The latter was therefore designated as "experimental" and subjected to standardization. Critical control points were established and three production runs were performed at bench scale. Triangle test showed no significant difference (α = 0.05). The control sauce was characterized by a color of 2.5 YR 6/14, consistency of 6.5 cm/30 at 32°C, pH 7.30, 9.50% salt, Aw of 0.932, 79.35% moisture content, 5.88% crude fat, 0.26% crude protein, 8.00% total available carbohydrates, 1.20% total dietary fiber and 5.31% ash. The experimental sauce, on the other hand, was characterized by a color of 2.5 YR 6/12, consistency of 5.5 cm/30 s at 32°C, pH 7.87, 8.50% salt, a water activity of 0.910, 83.15% moisture content, 6.57% crude fat, 0.04% crude protein, 2.18% total available carbohydrates, 3.86% total dietary fiber and 4.20% ash. Microbiological examination of the two sauces resulted to fairly low counts for aerobic bacteria, yeasts and molds and coliforms. The computed cost for a 300 g serving of the control sauce was P10.25 while that for the experimental is P12.57.